An Analysis of Standard of Living Index in West Bengal's Paschim Medinipur District: An Application of Average Correlation Method. Issue 2 (August 2019) - Pattanayek, Sanjoy Kumar; Mookherjee, Subikash; Mondal, Debasish
This article attempts to assess the role of standard of living (SL) as a development indicator belonging to the arena of famous Human Development Index for all the 29 blocks of undivided Paschim Medinipur district of West Bengal for the period 2005–2006 to 2014–2015. This purpose is fulfilled through the construction of Standard of Living Index (SLI) in which the weights of the underlying parameters are obtained by the application of iterative average correlation method (Mondal, Mookherjee, & Pattanayek, 2017, International Journal of Management and Development Studies, 6 [10], 28–36). The SLI, thus constructed, is observed to have high inter-block and high inter-temporal variations. These variations are explained by some of the selected factors of SL, namely, literacy rate, non-agricultural labour ratio, scheduled tribe ratio, population density (PD) and per capita food grain production by applying fixed effect model and random effect model in the panel data framework and by applying pooled data model to obtain their relative statistical importance on the basis of their ortho-partial correlation (Mondal, 2008, Communication in Statistics—Simulation and Computation, 37 [4], 713–730) and average correlation values. From the pooled regression results, it appears that the PD is the most important factor with the relative importance of 0.1496 out of 0.4987.